WRNIP1 Is Recruited to DNA Interstrand Crosslinks and Promotes Repair - Socha, Anna (Cell Rep, 2020)
The Fanconi anemia (FA) pathway repairs DNA interstrand crosslinks (ICLs). Many FA proteins are recruited to ICLs in a timely fashion so that coordinated repair can occur. However, the mechanism of this process is poorly understood. Here, we report the purification of a FANCD2-containing protein complex with multiple subunits, including WRNIP1. Using live-cell imaging, we show that WRNIP1 is recruited to ICLs quickly after their appearance, promoting repair. The observed recruitment facilitates subsequent recruitment of the FANCD2/FANCI complex. Depletion of WRNIP1 sensitizes cells to ICL-forming drugs. We find that ubiquitination of WRNIP1 and the activity of its UBZ domain are required to facilitate recruitment of FANCD2/FANCI and promote repair. Altogether, we describe a mechanism by which WRNIP1 is recruited rapidly to ICLs, resulting in chromatin loading of the FANCD2/FANCI complex in an unusual process entailing ubiquitination of WRNIP1 and the activity of its integral UBZ domain.